Impact of Teachers’ Professional Development on the Reading Achievement of Canadian Allophone Students - Azovide, Yesifa; Bouchamma, Yamina; Basque, Marc (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation, 2024)
This study examines the impact of teachers’ professional development on Canadian allophone students’ learning and reading performance levels. We used the data from the Pan-Canadian Assessment Program 2016 involving Grade 8/Secondary II Canadian allophone students (N = 2,244) and teachers in French and English Language Arts (N = 598). Our correlation results show that Canadian allophone students’ reading achievement was positively associated with teachers’ professional development activities such as academic pursuits (e.g., university courses) and marking or scoring sessions. The correlations also demonstrate that teachers’ professional practice of curriculum development had a positive influence on the learning levels of Canadian allophone students who were born in Canada, while teachers’ participation in professional learning communities had a positive effect on Canadian allophone students who were not born in Canada.